The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 4 age and the age of taking up Hospital work. The Committees on the whole do not think it desirable to alter the original drafting, but here state the criticism made for the benefit of readers. TRAINING AND GENERAL TRAINING. (Pages 24-25.) It was suggested that the period spent in the preliminary Training School should be reduced to two months, and the period of General Training extended to two years and ten months. The Committees prefer the proposal as it stands in the Report. CONDITIONS OF EMPLOYMENT OF FULLY-TRAINED NURSES. (Page 26.) Objection has been taken to the recommendation that the Profession should be organised on Trade Union lines, and it was suggested that the word "Vocational" should be substituted for the words "Trade Union." The Committees used the words "Trade Union" after very careful consideration, and gave their reasons in paragraph 3, page 27. After considering the criticisms they do not see any reason to alter the drafting, but would emphasise the fact that the main point to be aimed at is that the Profession should have a self-governing organisation of Nurses only. LIST OF ORGANISATIONS REPRESENTED AT THE CONFERENCE. NURSING AND KINDRED ORGANISATIONS. Association of Certificated Blind Masseurs. British College of Nurses. Central Council for District Nursing in London. Chartered Society of Massage and Medical Gymnastics. College of Nursing, Limited. General Nursing Council for England and Wales. Ling Association of Trained Teachers of Swedish Gymnastics. Nightingale Fund for Training of Nurses. Professional Union of Trained Nurses. Queen Victoria's Jubilee Institute for Nurses. Ranyard Nurses' Mission. Royal British Nurses' Association. Royal National Pension Fund for Nurses. Registered Nurses' Parliamentary Council. United Services Massage League. Matrons' Council of Great Britain and Ireland. TRADE UNIONS ADMITTING NURSES AND OTHER EMPLOYEES' ORGANISATIONS. Association of Hospital Matrons. National Asylum Workers' Union. Incorporated Association of Hospital Officers. National Federation of Professional Workers. National Union of General and Municipal Workers. National Poor Law Officers' Association. Poor Law Officers' Union. Sanitary Inspectors' Association. Transport and General Workers' Union. Women Sanitary Inspectors' and Health Visitors' Association. Poor Law Infirmary Matrons' Association. 126/TG/RES/X/1036A/14